The morality behind supporting crowdfunding campaigns for eco-hacktivists - Tetreault, Christie (Deviant behavior, 2024)
Hacktivism, the use of cyber-attacks for a social or political agenda, is becoming increasingly more common. We wanted to investigate if specific aspects of morality and subjective support for nonviolent eco-hacktivism would predict a willingness to donate to a crowdfunding campaign. A total of 350 participants responded to our cross-sectional study. To ensure the dimensionality of our morality components, we ran three principal component analyses (one for each actor in the hacktivism vignette) prior to running our regression model. Our regression model explained 41% of the variance in the willingness to donate to a crowdfunding campaign for the hacktivists. In addition to being younger, there was one significant predictor for each actor in our model. Perceiving the hackers to have higher moral-altruistic beliefs, feeling more moral-social connectivity to the spokesperson, and having more moral behavioral intention with the social media commentator were significant predictors. Preexisting beliefs toward clean water mediated the relationships between moral-altruistic beliefs of the hackers and moral-social connectivity to the spokesperson and a willingness to donate to the crowdfunding campaign. These findings suggest that different perceived morality toward varying actors may better predict support for hacktivism than others, and preexisting beliefs may assist in suppressing objective morality.